The hidden book in the Bible - Friedman, Richard Elliott (HarperSanFrancisco, 1998)
Contents: Renowned biblical sleuth and scholar Richard Elliot Friedman reveals the first work of prose literature in the world-a 3000-year-old epic hidden within the books of the Hebrew Bible. Written by a single, masterful author but obscured by ancient editors and lost for millennia, this brilliant epic of love, deception, war, and redemption is a compelling account of humankind's complex relationship with God. Friedman boldly restores this prose masterpiece-the very heart of the Bible-to the extraordinary form in which it was originally written